2010
DOI: 10.1111/j.1744-6198.2010.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Concept Analysis: Nurse-to-Nurse Lateral Violence

Abstract: This concept analysis demonstrates that nurse-to-nurse LV is nurse-to-nurse aggression with overtly or covertly directing dissatisfaction toward another. Origins include role issues, oppression, strict hierarchy, disenfranchising work practices, low self-esteem, powerlessness perception, anger, and circuits of power. The result of this analysis provides guidance for further conceptual and empirical research as well as for clinical practice. Organizations must learn how to eliminate antecedents and provide nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 25 publications
4
95
0
2
Order By: Relevance
“…Furthermore, teaching coping skills such as stress management and access to support resources to combat the negative impact of being victimized by bullying or observing others being bullied are critical. 24,25,38 Based on findings that nursing students' most common coping mechanism in response to being bullied was to do nothing, Celik and Bayraktar 30 encourage faculty to be equipped with the necessary skills and knowledge to effectively mentor and role model for students successful actions in response to bullying. These learning opportunities can be offered through an interactive class-based, small seminar and clinical conferences and can include simulation, role play, open discussion, and feedback.…”
Section: Academic Settingmentioning
confidence: 99%
“…Furthermore, teaching coping skills such as stress management and access to support resources to combat the negative impact of being victimized by bullying or observing others being bullied are critical. 24,25,38 Based on findings that nursing students' most common coping mechanism in response to being bullied was to do nothing, Celik and Bayraktar 30 encourage faculty to be equipped with the necessary skills and knowledge to effectively mentor and role model for students successful actions in response to bullying. These learning opportunities can be offered through an interactive class-based, small seminar and clinical conferences and can include simulation, role play, open discussion, and feedback.…”
Section: Academic Settingmentioning
confidence: 99%
“…10 Such behavior is intended to overtly, purposefully demean, humiliate, or diminish the victim's stature, resulting in social exclusion and marginalization in the workplace, which consequently leads to a power relationship in which the victim is emotionally controlled by the abuser. 11,12 Lateral violence among nurses typically takes the form of psychological abuse and includes a constellation of behaviors of abuse including gossiping, targeted personal jokes, ostracism, insults, unwarranted criticism, belittling, and verbal aggression. 13,14 It also includes covert sabotaging behaviors such as scheduling excessive workloads, misinformation, loss of records, violation of privacy, and breach of confidentiality.…”
Section: Lateral Violence Definedmentioning
confidence: 99%
“…The severity of nurse on nurse violence is well documented with resultant job dissatisfaction, high levels of absenteeism, professional disengagement and intent to resign (Longo 2007 Embree and White (2010), suggested that causes of lateral violence among nurses include lack of empowerment, authoritarian leadership style, learned hopelessness, negative workplace culture, toxic work environment, suppressed anger, shrinking resources, conflict avoiding culture, low self-esteem, personal behavior and strict hierarchical system. Freire (1970) Oppressed Group Model or oppression theory describes the hegemony of medicine relative to the predominantly female nursing profession and provides a theoretical framework for understanding lateral violence.…”
Section: Theoretical Frameworkmentioning
confidence: 99%